Hubungan Religiusitas Dengan Kepatuhan Penggunaan Obat dan Kualitas Hidup Pasien Hipertensi di Rumah Sakit Islam Sultan Agung - Ningrum, Yuyun Darma Ayu; Pratiwi, Agnes Febriyanti; Azzahroh, Nida Fauziyah (Sultan Agung Islamic University of Semarang, 2024)
Background: High blood pressure is a non-communicable disease but is called an unnoticeable killer or silent killer. Because the symptoms aren't veritably pronounced, but complications of high blood pressure can beget death and the prevalence of this complaint is adding every time. Someone who suffers from high blood pressure should always take drug regularly so that their blood pressure can be controlled and they can live a good life. Religiusity is the state in which a person behaves and is encouraged to bear in relation to religion. Religion can be used to reduce stress and depression which can lead to high blood pressure. Thus, this experimenters are interested in understanding the relationship between religiusity and drug compliance and quality of life in hypertensive cases at Sultan Agung Islamic Hospital. Methods: The research design used is quantitative correlational research with a cross-sectional approach. The number of samples in this study was 100. Results: The results of the study showed that there was a strong relationship between religiusity and the patients quality of life with p-value = 000 and r-value = 0.690 and there was a strong relationship between adherence to taking medication and the patients quality of life with p-value = 000 and r-value = 0.690. value = 0.552, but the relationship between adherence to taking medication and religiusity has a sufficient relationship with p-value = 000 and r-value = sufficient correlation. 0360. Conclusion: there was a strong relationship between religiusity and the patients quality of life, and between adherence to taking medication and the patients quality of life, but the relationship between adherence to taking medication and religiusity has a sufficient relationship.